Hasil Belajar Peserta Didik Kelas IV Sekolah Dasar dengan MenerapkanModel Pembelajaran Probing-Prompting - lena sari (Universitas Sriwijaya, 2019)
Abstrack: The purpose of this study was to improve the Learning Outcomes of Class IV Students of SD Negeri 17 Palembang in Giat Berusaha Meraih Cita-cita Subtheme by applying Probing-Prompting Learning Model. The research method used is Classroom Action Research (CAR) method which consists of 3 cycles; planning, implementation, observation and reflection. The subjects of this study were 26 students which divided into 10 male students and 16 female students from fourth grade class of SD Negeri 17 Palembang. Technique of collecting the data which is used a test in from of multiple choices. The tests are used in order to measure the level of completeness of learning outcomes that have been achieved by students in learing by using the Probing-Prompting learning model. The results of the research in the first cycle showed that there were 17 students who achieved the minimum completeness criteria (KKM) 70 with a classical completeness percentage of 65,38%. In the second cycle there was an improvment in students learning outcomes of 20 students with classical percentage for about 76,92%. In the third cycle there was also improvment in students learning outcomes, with the total 22 students passed the percentage of classical completeness for about 84,62%. It can be concluded that the Probing-Prompting learning model can improve learning outcomes of fourth grade in the sub-themes of Giat Berusaha Meraih Cita-cita at the 17 Palembang Elementary School.Keywords: Probing-Prompting Learning Model, Learning Outcomes. Abstrak: Penelitian ini bertujuan untuk meningkatkan hasil belajar peserta didik kelas IV SD Negeri 17 Palembang pada Subtema Giat Berusaha Meraih Cita-cita dengan Menggunakan Model Pembelajaran Probing-Prompting. Metode penelitian yang digunakan adalah Penelitian Tindakan Kelas (PTK) dengan 3 siklus tindakan yang terdiri dari perencanaan, pelaksanaan, observasi dan refleksi. Subjek penelitian adalah siswa kelas IV C SD Negeri 17 Palembang dengan jumlah 26 peserta didik terdiri dari 10 peserta didik Laki-laki dan 16 peserta didik Perempuan. Teknik pengumpulan data yang digunakan yaitu tes.Tes dilakukan untuk mengukur tingkat ketuntasan hasil belajar yang telah dicapai peserta didik pada pembelajaran dengan menggunakan model pembelajaran Probing-Prompting. Dari hasil penelitian pada siklus I diperoleh nilai yang mencapai kriteria ketuntasan minimal (KKM) 70 sebanyak 17 peserta didik dengan persentase ketuntasan klasikal 65,38%. Pada siklus II terjadi peningkatan hasil belajar peserta didik, sebanyak 20 peserta didik yang tuntas dengan ketuntasan klasikal sebesar 76,92%. Pada siklus III, terjadi peningkatan hasil belajar peserta didik, sebanyak 22 peserta didik yang tuntas dengan ketuntasan klasikal sebesar 84,62%. Dapat disimpulkan bahwa model pembelajaran Probing-Prompting dapat meningkatkan hasil belajar peserta didik kelas IV pada Subtema Giat Berusaha Cita-cita di SD Negeri 17 Palembang.Kata kunci: Model Pembelajaran Probing-Prompting, Hasil Belajar